PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH TAHUN 2017-2019 - Sigit Adi Pratama; LMS Kristiyanti; Sri Laksmi Pardanawati (Jurnal Akuntansi dan Pajak, 2022)
This study aims to determine the Effect of Regional Taxes, Regional Levies and General Allocation Funds on Capital Expenditures in Regency and City Governments in Central Java Province in 2017-2019. Capital Expenditure has an important role. This research is a quantitative research. The subject of this research is the district and city government in Central Java Province consisting of 35 districts and cities. The data used comes from the Report Realization of the 2017-2019 APBD. Data collection techniques using the method of documentation. Test requirements analysis using classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypothesis testing in this study used multiple linear regression analysis, t test (partial), F test (simultaneous), and the coefficient of determination (R2) test. Regional levies have no significant effect on Capital Expenditures. The General Allocation Fund variable has a significant effect on Capital Expenditures. Simultaneously Regional Taxes, Regional Levies, and General Allocation Funds have a significant effect on Capital Expenditures. So it can be concluded that if Regional Taxes and General Allocation Funds increase, it will increase the allocation of Capital Expenditures.